Selection criteria of motor insurance consumption - Rubayah Yakob,; Hendon Redzuan,; Mohamad Abdul Hamid, (Penerbit ukm, 2007)

(untitled)
In Malaysia, motorists are required by law to insure minimum coverage for their automobiles. However, the policy they own and the insurer they choose may not suit their needs. This study examines several characteristics which influence consumers’ selection of auto insurance policy and their loyalty to one insurer. Data were collected from a survey of 178 randomly selected respondents. A chi-square analysis was conducted to determine the relationship between age, race, gender, education background and automobiles’ market value to the selection of auto insurance policy. In addition, the relationship between premium, dividend, insurer’s internal factors, claim services and non-claim services to the loyalty of the consumer are also tested using the chi-square and Spearman rank test. The results indicate that education background and market value of the automobile are significant characteristics in selecting auto insurance policy, while premium, dividend, insurer internal factors, claim and non-claim services are not related to the loyalty of the consumer. The study reveals that such results were attributed to the lack of industry information and the role of auto salesperson. For future research, the issue should be examined with a larger set of data to represent the industry better